10.6 Design, Construction, and Maintenance of Haul Roads - Thompson, Roger (Society for Mining, Metallurgy, and Exploration, 2011)
In truck-based hauling systems, the mine haul road network is a critical and vital component of the production process. As such, under-performance of a haul road will impact immediately on mine productivity and costs. Operations safety, productivity and equipment longevity are all dependent on well-designed, constructed and maintained haul roads (Thompson and Visser, 1999). The mine haul road is an asset and should, in conjunction with the haul trucks using the road, be optimally designed and its routine maintenance managed accordingly. An ad-hoc or empirical approach to haul road design is generally unsatisfactory because it has the potential for over-expenditure, both on construction and operating costs, arising due to; • The over-design and specification of short term low-traffic volume roads • The under-design, leading to excessive operating and road maintenance costs and premature failure in the case of longer-term higher-volume roads.Economy of scale and the increase in haul truck payload has so far seen the ultra-class truck (220t and larger) population rise to over 40% of all mine trucks used (Gilewicz,2006). With this increasing size, haul road performance can be compromised, resulting excessive total road-user costs; translating to an increase in cost per ton hauled, but also indirectly as reduced production rates and vehicle and component service life. Truck haulage costs can account for up to 50% of the total operating costs incurred by a surface mine and any savings generated from improved road design and management benefit the mining company directly as a reduced cost per tonne of material hauled. Central to the cost of truck hauling is the concept of rolling resistance (expressed here as a percentage of Gross Vehicle Mass (GVM)). It is a measure of the extra resistance to motion that a haul truck experiences and is influenced by tire flexing, internal friction and most importantly, wheel load and road conditions. Empirical estimations of rolling resistance based on tire penetration specify typically a 0.6% increase in rolling resistance per centimeter tire penetration into the road, over and above the 1.5% (radial and dual wheel assemblies) to 2% (cross-ply or single wheel assemblies) minimum resistance. In addition to tire penetration, road surface deflection or flexing will also generate similar results, with the truck tire running “up-grade” as the deflection wave pushes ahead of the vehicle. Taking an electric-drive rear-dump ultra-truck of 376t (GVM) as an example, on a ramp road with a basic rolling resistance of 2%, an additional 1% rolling resistance will reduce truck speed by 10-13%, whilst on a flat surface road, the truck speed will reduce by between 18-26%.Whilst many concepts from highway engineering can be adapted to the design, construction and management of mine roads, significant differences in applied loads, traffic volumes, construction material quality and availability, together with design life and road-user cost considerations, mitigate for a tailored design solution for mine haul roads.